Twin Challenges in Türkiye: Exclusive Breastfeeding Rates and Predictors of Breastfeeding Duration in a Tertiary Care Center - Ayça Kömürlüoğlu; Gökçe Çıplak (Children, 2025)
Objectives: This study aimed to evaluate exclusive breastfeeding (EBF) rates and the duration of breastfeeding among mothers of twins and to identify the maternal, neonatal, and social factors associated with these outcomes. Methods: This retrospective cross-sectional study included 153 mothers of twin infants who were delivered at a tertiary hospital. Data were obtained from medical records and postnatal telephone interviews. Univariate analyses were performed to assess associations with EBF and breastfeeding duration, while multiple linear regression was performed to identify the independent predictors of breastfeeding. Results: The EBF rate within the first six months was 15%, and the mean breastfeeding duration was 10.5 ± 8.3 months. Tandem breastfeeding was positively associated with breastfeeding duration (β = 5.80; 95% CI: 3.51 to 8.10; p < 0.001), whereas bottle feeding showed a strong negative association (β = −9.49; 95% CI: −12.88 to −6.10; p < 0.001). Infants born before 34 weeks had significantly shorter breastfeeding durations, higher rates of NICU admission and respiratory support, and received less skin-to-skin contact and breastfeeding counselling compared to term infants (p < 0.05). Conclusions: Exclusive breastfeeding rates among mothers of twins remain low. Encouraging tandem breastfeeding, reducing bottle use, and providing tailored lactation support—particularly for mothers of preterm infants—may improve breastfeeding outcomes. Breastfeeding support should be adapted according to gestational age in neonatal care.